A Peran Penguatan Konselor Dalam Meningkatkan Kualitas Pendidikan di Era Globalisasi: Peran Penguatan Konselor Dalam Meningkatkan Kualitas Pendidikan di Era Globalisasi - Susandi, Ari (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
Education is the provision of the state to achieve an independence, education is one of the icon of the state to be able to create generations of education that are reliable and have high competitiveness and good character to face society and the development of an increasingly advanced era. In this case our role as an educator or counselor should be able to provide effective guidance and learning to learners according to age and stage of child development. Counselors as academic counselors who are in the scope of education should be able to create an educational atmosphere of learning as a means of obtaining quality human resources that are superior and able to compete in the international arena in the face of globalization. The link between counselor and children's education in counseling counseling is expected to create a world that is able to appreciate the talent, creativity of children and develop intellectual and child's ability to form a good output and outcome, and must be able to face the challenge of education in the 21st century which later Indonesia Should really have a good quality of education in addition to having educational goals and curriculum are patterned Indonesia so that the need for renewal of the system of education, qualifications of the competence of educators. Where this rule will be able to bring the educators can maximize the purpose of learning in order to be able to guide learners in shaping the character and have a patriotism soul that will be able to build a country that has quality Indoneisa world-quality human resources. The role of strengthening the counselor in improving the quality of education has many advantages that bring Indonesia in the globalization competition.Keywords: Reinforcement of counselor, quality of education, globalization era